SEXIST LANGUAGE FROM TWO TYPICAL ASPECTS: SEXISM IN WORDS AND SEXISM IN PROVERBS - Marlina Tampubolon; Dwi Pebrina Sinaga; Nurul Husnah Harahap (Sean Institute, 2021)
This aim is to analysis the bias in favor of one sex and thus treats the other sex in a discriminatory manner. In most cases, the bias is in favor of men and against women. This paper firstly discusses sexist language from two typical aspects: sexism in words and sexism in proverbs. Then it emphasizes that owing to Women’s Liberation Movement in Western Countries, women’s social status has been bettered, and such super masculine phenomenon in English is being alleviated accordingly. In order to illustrate the two issues clearly, many interesting examples are given.